Tissue signatures influence the activation of intrahepatic CD8+ T cells against malaria sporozoites - Morrot, Alexandre; Rodrigues, Maurício M. (Frontiers in Microbiology, 2014)
Plasmodium sporozoites and liver stages express antigens that are targeted to the MHC-Class I antigen-processing pathway. After the introduction of Plasmodium sporozoites by Anopheles mosquitoes, bone marrow-derived dendritic cells in skin-draining lymph nodes are the first cells to cross-present parasite antigens and elicit specific CD8+ T cells. One of these antigens is the immunodominant circumsporozoite protein (CSP). The CD8+ T cell-mediated protective immune response against CSP is dependent on the interleukin loop involving IL-4 receptor expression on CD8+ cells and IL-4 secretion by CD4+ T cell helpers. In a few days, these CD8+ T cells re-circulate to secondary lymphoid organs and the liver. In the liver, the hepatic sinusoids are enriched with cells, such as dendritic, sinusoidal endothelial and Kupffer cells, that are able to cross-present MHC class I antigens to intrahepatic CD8+ T cells. Specific CD8+ T cells actively find infected hepatocytes and target intra-cellular parasites through mechanisms that are both Interferon-g-dependent and -independent. Immunity is mediated by CD8+ T effector or effector-memory cells and, when present in high numbers, these cells can provide sterilizing immunity. Human vaccination trials with recombinant formulations or attenuated sporozoites have yet to achieve the high numbers of specific effector T cells that are required for sterilizing immunity. In spite of the limited number of specific CD8+ T cells, attenuated sporozoites provided multiple times by the endovenous route provided a high degree of protective immunity. These observations highlight that CD8+ T cells may be useful for improving antibody-mediated protective immunity to pre-erythrocytic stages of malaria parasites.